Language and conceptual change strategies in physics teaching - Nkopodi, Nkopodi (My University, 2014)
This study considers pupils understanding of the topic of pressure together with some of the language problems they experience. Some language strategies which may be used by teachers to remedy these problems are identified. The sample is mainly standard 7 black children (aged about 13, N = 431) in a second language situation in South Africa. The black children spoke mainly Sepedi (also known as Northern Sotho) at home. However two classes of English first language pupils and teachers were involved in the initial stages of the research. During this initial investigations ten lessons and interviews were tape recorded and language and conceptual difficulties identified. Then interviews were conducted with 4 teachers and 10 pupils. Anecdotes in the interviews showed language difficulties and conceptual difficulties which could be attributed to language. These were then used in the development of worksheets for pupils and a teachers’ guide. During the initial investigations of the misconceptions, an open test was administered to graduate student teachers as a convenience sample because of the unrest situation caused by the political climate of the day at the schools. This open test was then converted into a multiple choice form and administered to a large sample of school pupils. Respondents to the tests were also required to give reasons for their answers. The test was first piloted with student teachers and physics bridging course students at a university, before the main pilot with school pupils. Further misconceptions unfolded during the piloting process. The final test was administered both as a pre-test and as a post-test to an experimental and a control group, a total of 571 pupils. The reasons given for the correct answers were coded so that quantitative analysis could be used. In general, performance was poor both in the experimental and the control groups despite intervention. In an effort to understand effects of language competence on performance in the conceptual test, four language tests which were previously used in an English 1st language situation in the UK were modified and each administered to 25% of the sample. These language tests however proved very difficult for the pupils. Scores were low and no correlation could be found between the language tests and the conceptual tests. Language difficulties were however identified in single incidences from teachers as well as pupils. Some of the language difficulties led to conceptual difficulties. In conclusion many pupils have difficulty in understanding the concepts in the topic hydrostatic pressure. Some of these difficulties may be compounded by language problems.